Lifetime improvement of visual sensor networks for target coverage through uniform energy consumption. (2nd January 2014) - Hosseini, Mojtaba; Dehghan, Mehdi; Pedram, Hossein
In this paper, a novel method is proposed for inducing uniformity in energy consumption across the entire network area. This method prolongs the durability of the target coverage task. Moreover, it is shown that the optimised selection of the sensors in each timeslot does not lead to an optimum selection across the lifetime of the network due to non–uniformity in energy consumption pattern. Uniformity control is achieved using the sensors' panning capability to select the sensing area. The major notion of energy uniformity in this paper is typified with the network area sections level. For this criterion, sensor selection has been modeled as a binary integer programming (BIP) problem, and optimal solutions have been obtained for both point target model and circular target model which are used in k–coverage and full–angle coverage, respectively. Furthermore, a distributed algorithm has also been proposed. Experimental results demonstrate that exerting uniformity control can significantly increase the lifetime of the network.